Pengaruh Beban Kerja dan Fasilitas Kerja Terhadap Kinerja Keagenan di PT. IDT Trans Agency Cabang Sungai Danau - Hutagalung, Rony; Retnandari, Septina Dwi; Alimatussa’diyah, Alimatussa’diyah (Jurnal Maritim Polimarin, 2024)
This research began with fluctuations in ship visits as a result of employee performance. The performance generated by employees appears to be suboptimal due to factors such as high workload resulting from an inadequate number of employees compared to the volume of ship visits handled by the company, compounded by insufficient facilities such as company transportation. This study aims to determine the influence of workload and workplace facilities on agency performance. The method employed in this research is quantitative, utilizing data collection through questionnaires distributed to 32 employees as respondents at PT. IDT TRANS AGENCY, Sungai Danau Branch. Data analysis was conducted using SPSS (Statistical Package for The Social Sciences) version 24. The results of this research indicate that there is an influence of workload and workplace facilities on performance with an adjusted R square value of 0.784. This means that workload and workplace facilities contribute to 78,4% of the performance, while the remaining part as many as 21,6% is influenced by other factors which is not tested in this study.